DIGITAL MARKETING 5-GENERATION TECHNOLOGY AND ITS ACCEPTANCE BEHAVIOR - Ismail, Muhammad; Islam, K. M. Anwarul; Zohaib, Muhammad; Hussain, Riaz; Tahir, Muhammad Yasir; Ijaz, Muhammad; Hassan, Zuhaib (International Journal of Marketing Research Innovation, 2021)
Cumulative usage of digital media by customers, most of the companies are exploitation the digital marketing to get the access towards their target clients and markets. With the development of mobile technologies, mobile services have become an essential part of people's lives. After an ample research a series of advance experimentation and development, the mobile technology emerged and enters into more advance 5-G period.  The purpose of this study is to examine various marketing strategies and investigate Pakistani consumers’ approach towards the existing mobile services and classify the factors affecting their preferences towards 5-G acceptance. With a view to accomplish this study. A cross-sectional technique with the help of questionnaire was used to collect data. 15 to 45 years age people male & female were our targeted audience from the different places of Multan city (Punjab province) Pakistan. 500 questionnaires were distributed and received (n) 430 which were completed by all aspects. (F=58%) & (M=42%). SPSS, (22nd) version used for data analysis. After the data analysis and discussion, (r) correlation was retrospection that (DV), (IV) & (MV) have a strong and positive relationship between each other. (r2) regression analysis also showed the confident, positive and durable relation among the all variables. Results show that the convenience, price, service quality, self-efficacy and value are the factors affecting consumers’ acceptance in the presence of a moderator that is perceived usefulness. Suggested an extended TAM (Technology Acceptance Model) for checking consumer’s behavior towards 5-G mobile services. Consumers should adopt the new technology and utilize it for the benefits of him/herself and for the community, nation and state.